À l’aube de la bibliographie : les références externes dans les dictionnaires latins, 1480–1545 - Furno, Martine (Renaissance and Reformation / Renaissance et Réforme, 2011)
The appearance of printed text resulted in changes to the way text is accessed, which leads to the question of whether these changes modified scholarly practice; and if so, how? The following article examines this question in a particular context—that of dictionaries and encyclopedias, referencing classical citations as guarantors and examples. The article defines the evolution of three important witnesses in this domain from the end of the fifteenth century to the first part of the sixteenth: the Cornu Copiae by Niccolo Perotti, the Commentarii linguae latinæ by Etienne Dolet, of which two tomes appeared in 1536 and 1538, and the Thesaurus Latinae Linguae by Robert Estienne, in its three versions from 1531, 1536, and 1543. These three books represent the same type of object: language dictionaries, aimed towards a specific public of advanced learners, or the learned. In fact, the material weight of book fabrication, the difficulty from then on of collecting masses of texts, the new study conditions, the sheer quantity of texts available, and the famous temptation of universality, made the practice of regulation and of precise referencing an urgent necessity. The position of learned printers of Estienne’s generation was crucial: they helped create and then make commonplace certain material norms that are now so much part of our intellectual habit that we sometimes forget their material origin.